The Jones-Mueller transformation - Hunte, Carlos (Array, 2008)
Summary: A simple transformation allows the construction of the real-valued Mueller matrix from the complex-valued Jones matrix. The transformation is tested on the Jones matrices of optical devices to produce the corresponding Mueller matrices. The Stokes vector is also deduced from the corresponding Jones vector